A model to facilitate collaborative social support for pregnant students in secondary schools - Matlala, Sogo F. (Journal of Multidisciplinary Healthcare, 2017)
Pregnancy among secondary school students remains a public health problem and is associated with school dropout as well as poor maternal and child health outcomes. Schools in South Africa no longer expel pregnant students as was the case before 2000. Instead, the government encourages them to remain in class to complete their education, but pregnant students often face stigma, and some drop out of school as a result. To remain in class and access antenatal care, pregnant students require social support from teachers, parents and professional nurses. Unfortunately, teachers, parents and professional nurses support pregnant students on an ad hoc basis, and this calls for a model to facilitate collaborative social support. The purpose of this paper is to present and describe a model to facilitate collaborative social support for pregnant students attending secondary schools in South Africa, using the model description steps of Chinn and Kramer. The model is designed as a tool to enable pregnant students to remain in school, attend antenatal care and in the end, deliver healthy babies. The professional nurse, as a member and leader of the school health team which visits secondary schools to provide a package of school health services, is the agent or facilitator of the model. Keywords: communication, health team, learner pregnancy, maternal and child health, school health services, social network
Article published in the Journal of Multidisciplinary Healthcare 2017:10 383-389
Keywords: Communication; Health team; Learner pregnancy; Maternal and child health; School health services; Social network; Pregnant students; Child health services; Maternal health services; Pregnancy